Porous body

A spherical porous body with optimized pore structure and composition improves gas diffusivity and mechanical strength by employing Cu-containing pores and a three-dimensional network, ensuring effective gas diffusion and handling.

JP2025007066APending Publication Date: 2025-01-17NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023108225
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing porous bodies lack sufficient pore design, which affects both mechanical strength and gas diffusion.

Method used

A spherical porous body with Cu-containing pores of 0.5 mm to 10 mm diameter, featuring a three-dimensional network structure, average pore diameters between 39 nm and 299 nm, and a mode of pore volume distribution between 133 nm and 389 nm, with open porosity between 40% and 70%, and optionally containing Ca, Na, Zn, and Al, is developed.

Benefits of technology

The solution enhances gas diffusivity within the pores while maintaining mechanical strength, as demonstrated by improved gas responsiveness and compressive strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007066000001_ABST
    Figure 2025007066000001_ABST
Patent Text Reader

Abstract

To provide a porous body which can improve diffusivity of gas in pores while securing the mechanical strength.SOLUTION: A porous body includes Cu, has pores, and is in a spherical shape with a diameter of 0.5 mm to 10 mm, wherein an average pore diameter exists between 39 nm and 299 nm and a mode value in a pore volume distribution exists between 133 nm and 389 nm, in the pore volume distribution with a pore diameter ranging from 3.6 nm to 5,000 nm as measured by a mercury intrusion technique.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous body having pores. [Background technology]

[0002] Prior art relating to a spherical porous body containing Cu and having pores with a diameter of 0.5 mm to 10 mm is disclosed in Patent Document 1. The pores of the porous body are related to the diffusion of gases that affect catalytic reactions, adsorption, combustion, reduction, etc., and the mechanical strength of the porous body. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2014-533230 Summary of the Invention [Problem to be solved by the invention]

[0004] The prior art has poor pore design which affects mechanical strength and gas diffusion.

[0005] The present invention has been made to solve this problem, and an object of the present invention is to provide a porous body capable of improving the diffusibility of gas within the pores while ensuring mechanical strength. [Means for solving the problem]

[0006] A first aspect for achieving this object is a spherical porous body containing Cu and having pores with a diameter of 0.5 mm to 10 mm, in which, in a pore volume distribution in the pore diameter range of 3.6 nm to 5000 nm measured using mercury intrusion porosimetry, the average pore diameter is between 39 nm and 299 nm, and the mode of the pore volume distribution is between pore diameters of 133 nm and 389 nm.

[0007] In the second embodiment, the first embodiment includes a skeleton having a three-dimensional network structure, and Cu constitutes a part of the skeleton.

[0008] In a third aspect, in the first or second aspect, the carbon content is 1 wt % or less.

[0009] In a fourth aspect, in any one of the first to third aspects, the open porosity calculated by the mercury porosity method in a pore diameter range of 3.6 nm to 5000 nm is between 40% and 70%.

[0010] A fifth aspect is any one of the first to fourth aspects, further comprising at least two of Ca, Na, Zn, and Al.

[0011] The sixth embodiment is used in the addition of hydrogen using an oxocarbon as a raw material in any one of the first to fifth embodiments. Effect of the Invention

[0012] According to the present invention, in the pore volume distribution in the pore diameter range of 3.6 nm to 5000 nm measured using mercury intrusion porosimetry, the average pore diameter of the porous body is between 39 nm and 299 nm, and the mode of the pore volume distribution is between pore diameters of 133 nm and 389 nm, so that the mechanical strength of the porous body can be ensured while improving the gas diffusivity in the pores. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram of a porous body according to one embodiment. [Diagram 2] 1 is an example of a Log differential pore volume distribution of a porous body. [Diagram 3] 13(a) shows the test results of the gas responsiveness of the porous body of sample No. 1, and (b) shows the test results of the gas responsiveness of the porous body of sample No. 12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Fig. 1 is a schematic diagram of a porous body 10 in one embodiment. Fig. 1 shows an enlarged view of a portion of the surface of the porous body 10. The porous body 10 includes a skeleton 11 having a three-dimensional network structure. Pores 12 are provided between the skeletons 11.

[0015] The outer shape of the porous body 10 is spherical. A spherical shape means a spherical or pseudo-spherical shape. A pseudo-spherical shape includes an ellipsoid, an egg shape, and a gourd shape. A pseudo-spherical shape includes a spherical, ellipsoid, an egg shape, or a gourd shape having an uneven surface. If the porous body 10 is spherical, it is preferable because the filling rate can be increased when the porous body 10 is packed into a container or the like.

[0016] The diameter of the porous body 10 is in the range of 0.5 mm to 10 mm. The diameter of the porous body 10 refers to at least one of the major axis and the minor axis when the porous body 10 is ellipsoidal or oval, the diameter of the constricted part or the diameter outside the constricted part when the porous body 10 is gourd-shaped, and the diameter including the convex part when the porous body 10 has an uneven surface. If the diameter of the porous body 10 is less than 0.5 mm, the porous body 10 is likely to scatter, and if the diameter exceeds 10 mm, the open porosity of the porous body 10 is likely to decrease. It is preferable that the diameter of the porous body 10 is in the range of 0.5 mm to 10 mm because the porous body 10 is easy to handle.

[0017] The porous body 10 is a sintered body containing Cu. It is preferable that a part of the skeleton 11 of the porous body 10 is constituted by Cu or copper oxide. This is because the proportion of Cu in the porous body 10 can be increased. The fact that Cu or copper oxide constitutes a part of the skeleton 11 does not include a case where particles containing Cu are attached to the surface of the skeleton 11 or where Cu is permeated into the skeleton 11, but means that Cu or copper oxide is responsible for a part of the mechanical strength of the skeleton 11. The copper oxide contained in the porous body 10 changes to copper when the porous body 10 is reduced. The proportion of Cu in the porous body 10 is preferably 20% by mass or more, more preferably 30% by mass or more, and particularly preferably 40% by mass or more.

[0018] An example of a method for producing the porous body 10 will be described. First, a raw material powder containing Cu and an alginate aqueous solution are prepared. Next, a liquid in which the raw material powder is dispersed in the alginate aqueous solution is dropped into a polyvalent metal salt aqueous solution to obtain a gel-like material. Since the liquid dropped into the polyvalent metal salt aqueous solution gels in a short time, a spherical gel-like material can be easily obtained. After the gel-like material is taken out of the polyvalent metal salt aqueous solution, it is washed with water, dried, and then fired in the air to obtain a porous body 10 having pores 12. Cu is precipitated in the skeleton 11 of the porous body 10 by reducing and firing the porous body 10.

[0019] The alginate aqueous solution is an aqueous solution in which an alginate is dissolved in water. Examples of the alginate include alkali metal salts of alginic acid such as Li, K, and Na. The raw material powder contains a material that constitutes a part of the skeleton 11 of the porous body 10. The raw material powder contains copper oxide, and may contain one or more of aluminum oxide, zinc oxide, chromium oxide, magnesium oxide, cerium oxide, boron oxide, molybdenum oxide, and zirconium oxide in addition to copper oxide depending on the application of the porous body 10. The polyvalent metal salt aqueous solution is an aqueous solution in which a polyvalent metal salt is dissolved in water. Examples of the polyvalent metal salt include halides (excluding fluorides), nitrates, and acetates of metals such as Ca, Mg, and Fe.

[0020] The porous body 10 can contain at least two of Ca, Na, Zn, and Al. For example, Ca, Zn, and Al are derived from polyvalent metal salts, and Na is derived from alginate. When the raw material powder contains one or more elements of Ca, Na, Zn, and Al, the porous body 10 also contains these elements. However, the inclusion of these elements in the porous body 10 may indicate that the porous body 10 was produced through a gel-like material obtained by dropping a liquid in which the raw material powder was dispersed in an alginate aqueous solution into an aqueous solution of a polyvalent metal salt. By producing the porous body 10 through a gel-like material, a spherical porous body 10 can be easily produced.

[0021] There is no limit to the uses of the porous body 10, but one of the uses of the porous body 10 is as a catalyst. The porous body 10 is used as a catalyst for decomposing greenhouse gases such as nitrous oxide, and for adding hydrogen using oxocarbon as a raw material. For example, a Cu-cerium oxide catalyst is highly active in decomposing nitrous oxide. Oxocarbons are inorganic compounds consisting only of carbon and oxygen, and examples of such compounds include carbon monoxide, carbon dioxide, carbon suboxide, and mellitic anhydride. Methane, paraffins, olefins, methanol, higher alcohols, aromatic hydrocarbons, aldehydes, ketones, and the like are synthesized by the hydrogenation reaction of carbon monoxide. For example, a Cu-ZnO-Al2O3 catalyst is highly active in synthesizing methanol.

[0022] FIG. 2 is an example of a Log differential pore volume distribution of a porous body 10 obtained by mercury intrusion porosimetry. The pore volume of the porous body 10 is measured in the range of pore diameters from 3.6 nm to 5000 nm. The Log differential pore volume distribution is obtained by dividing the differential pore volume, which is the increment in the pore volume in each section, by the difference in the logarithm of the pore diameter, and plotting this against the average pore diameter in each section. Distribution 13 is an example of a Log differential pore volume distribution of a porous body 10 having a mode 14 near a pore diameter of 380 nm. Distribution 15 is an example of a Log differential pore volume distribution of a porous body 10 having a mode 16 near a pore diameter of 140 nm.

[0023] In the porous body 10, the most frequent value of the pore volume distribution is between 133 nm and 389 nm in pore diameter, and the average pore diameter is between 39 nm and 299 nm. The average pore diameter d (overbar) is calculated by applying the measurement results of the differential pore volume distribution to the following formula. i is the pore radius r for each measurement i is the volume of the pores having

[0024]

number

[0025] If the mode of the pore volume distribution is in the range of pore diameters less than 133 nm or the average pore diameter is less than 39 nm, the gas diffusibility in the pores 12 decreases. In contrast, if the mode of the pore volume distribution is in the range of pore diameters equal to or greater than 133 nm and the average pore diameter is equal to or greater than 39 nm, the gas diffusibility in the pores 12 improves.

[0026] If the pore volume distribution mode is in a range where the pore diameter exceeds 389 nm, or if the average pore diameter exceeds 299 nm, the mechanical strength of the porous body 10 decreases. In contrast, if the pore volume distribution mode is in a range where the pore diameter is 389 nm or less, and the average pore diameter is 299 nm or less, the mechanical strength of the porous body 10 can be ensured.

[0027] From the viewpoint of ensuring the gas diffusivity of the pores 12 and the mechanical strength of the porous body 10, the open porosity of the porous body 10 determined by the mercury porosity method is preferably in the range of 40% to 70%. If the open porosity is less than 40%, the gas diffusivity tends to decrease, and if the open porosity is more than 70%, the mechanical strength of the porous body 10 tends to decrease.

[0028] The carbon content of the porous body 10 is preferably 1 wt % or less in order to prevent the pores 12 from being blocked by the carbon contained in the porous body 10. The carbon content of the porous body 10 is determined by a carbon / sulfur analyzer that heats the porous body 10 in an oxygen stream and determines the carbon concentration from the infrared absorption of the generated gas. EXAMPLES

[0029] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0030] (Sample No. 1-11) Raw material powders prepared by coprecipitation so that the powders of copper oxide, zinc oxide, aluminum oxide, and zirconium oxide were in a ratio of 40:30:15:15 (mass ratio) were calcined at 400°C in air. The calcined raw material powders and a pore former consisting of acrylic fine particles were dispersed in an aqueous solution in which sodium alginate was dissolved in purified water to prepare a liquid. The prepared liquid was dropped into an aqueous calcium chloride solution to prepare a spherical gel. The gel was taken out, washed with water, dried, and then calcined in air to obtain a porous body in Sample No. 1-11. The ratio of raw material powder in the liquid (wt%), the ratio of pore former to raw material powder (vol%), the concentration of sodium alginate in the liquid (wt%), the concentration of calcium chloride aqueous solution (wt%), the calcination temperature of the gel (°C), and the diameter of the porous body (mm) are shown in Table 1.

[0031] [Table 1]

[0032] (Sample No. 12) Raw material powders prepared by coprecipitation so that the powders of copper oxide, zinc oxide, and aluminum oxide were in a ratio of 50:40:10 (mass ratio) were sintered in air at 400°C. After graphite was added as a lubricant to the sintered raw material powder, pellets were formed by uniaxial pressing to obtain cylindrical porous bodies with a diameter of 3 mm and a thickness of 3 mm.

[0033] (Sample No. 13) The powders of copper oxide, zinc oxide, aluminum oxide and zirconium oxide were weighed out in a ratio of 40:30:15:15 (mass ratio) and mixed in a mortar to obtain a raw material powder. A liquid was prepared by dispersing the raw material powder in an aqueous solution of sodium alginate dissolved in purified water. The prepared liquid was dropped into an aqueous calcium chloride solution to prepare a spherical gel. The gel was taken out, washed with water, dried, and then fired in the air to obtain a porous body in Sample No. 13. The ratio of the raw material powder in the liquid (wt%), the concentration of sodium alginate in the liquid (wt%), the concentration of the aqueous calcium chloride solution (wt%), the firing temperature of the gel (℃), and the diameter of the porous body (mm) are shown in Table 1.

[0034] (Measurement of pore volume distribution) The pore volume distribution of porous bodies with pore diameters ranging from 3.6 nm to 5000 nm was measured using a mercury intrusion porosimeter, and the average pore diameter (nm), the mode of the log differential pore volume distribution (nm), and the pore volume (cm 3 The results are shown in Table 1.

[0035] (Measurement of carbon content) The carbon content (wt%) of the porous bodies was measured using a carbon / sulfur analyzer, and the results are shown in Table 1.

[0036] (Strength of porous bodies) The compressive strength of the porous body was measured by a uniaxial compression test in which a compressive load was applied to the porous body without any lateral pressure. 2 The above samples are rated as A, with a compressive strength of 7kg·f / cm 2 Samples with less than this were rated as B. The results are shown in Table 1.

[0037] (Gas responsiveness of porous materials) The porous body was calcined to reduce the copper oxide contained in the porous body to metallic Cu, and then the gas response of the porous body was evaluated by N2O pulse measurement utilizing the oxidation of metallic Cu by nitrous oxide (N2O+2Cu→Cu2O+N2) using a normal pressure flow system. As a pretreatment for the N2O pulse measurement, the porous body was treated in O2 for 15 minutes at 400°C to clean its surface, and then treated in H2 for 15 minutes at 400°C to reduce the copper oxide contained in the porous body to metallic Cu.

[0038] After pretreatment, the gas generated was analyzed when a pulse gas containing 5% nitrous oxide was passed through a carrier gas (He) flow at 50°C. The amount of porous body in the system was 60 mg. 1 mL of pulse gas was passed through every 10 minutes. A gas chromatograph was used to analyze the nitrous oxide and nitrogen contained in the generated gas.

[0039] Samples in which the nitrogen content of the generated gas fell to 50 ppm or less after seven pulse gas flows were rated as A, and samples in which this did not happen were rated as B. The results are shown in Table 1. Figure 3(a) shows the test results for the gas responsiveness of the porous body for sample No. 1, which was rated as A. Figure 3(b) shows the test results for the gas responsiveness of the porous body for sample No. 12, which was rated as B.

[0040] The fact that the nitrogen in the generated gas of the sample judged as A was below 50 ppm indicates that the metal Cu in the pores was oxidized in a short time due to the good diffusion of the pulse gas in the pores, and nitrogen generation stopped.The sample judged as B indicates that the diffusion of the pulse gas in the pores was poor, and the oxidation of the metal Cu by nitrous oxide progressed little by little, and nitrogen generation continued.

[0041] (evaluation) According to Table 1, samples in which the mode of the pore volume distribution was in the pore diameter range of 133 nm or more and the average pore diameter was 39 nm or more were judged to have an A for both mechanical strength and gas responsiveness. This shows that by designing the average pore diameter and the mode of the pore volume distribution of the porous body, it is possible to improve the diffusivity of gas within the pores while ensuring the mechanical strength of the porous body.

[0042] The present invention has been described above based on an embodiment, but the present invention is in no way limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.

[0043] In the examples, the gas diffusivity of the porous body was evaluated using He containing nitrous oxide, but it is presumed that evaluations using other gas species will be similar. This is because the pore diameter of the porous body 10 is sufficiently smaller than the mean free path of the gas molecules, which is determined by the type and density of the molecules, and therefore the diffusion of the gas in the pores 12 is caused by collision between the gas molecules and the walls of the pores 12, regardless of the gas species. [Explanation of symbols]

[0044] 10 Porous bodies 11 Skeleton 12 Pore

Claims

1. A spherical porous body containing Cu, having pores and a diameter of 0.5 mm to 10 mm, In the pore volume distribution measured by mercury intrusion porosimetry in the range of pore diameters from 3.6 nm to 5000 nm, the average pore diameter is between 39 nm and 299 nm; A porous body in which the most frequent value of the pore volume distribution is the pore diameter between 133 nm and 389 nm.

2. It contains a three-dimensional mesh structure skeleton, The porous body according to claim 1 , wherein the Cu constitutes a part of the skeleton.

3. 3. The porous body according to claim 1, wherein the carbon content is 1 wt % or less.

4. 3. The porous body according to claim 1, wherein the open porosity calculated by the mercury porosity method in a range of pore diameters from 3.6 nm to 5000 nm is between 40% and 70%.

5. 3. The porous body according to claim 1, further comprising at least two of Ca, Na, Zn and Al.

6. 3. The porous body according to claim 1, which is used for adding hydrogen to an oxocarbon as a raw material.

Citation Information

Patent Citations

  • Composite containing crystalline hybrid nanoporous powder and method for producing the same

    JP2014533230A